2020
DOI: 10.1002/pst.2053
|View full text |Cite
|
Sign up to set email alerts
|

Prior distributions for variance parameters in a sparse‐event meta‐analysis of a few small trials

Abstract: SummaryIn rare diseases, typically only a small number of patients are available for a randomized clinical trial. Nevertheless, it is not uncommon that more than one study is performed to evaluate a (new) treatment. Scarcity of available evidence makes it particularly valuable to pool the data in a meta‐analysis. When the primary outcome is binary, the small sample sizes increase the chance of observing zero events. The frequentist random‐effects model is known to induce bias and to result in improper interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 42 publications
(73 reference statements)
0
30
0
Order By: Relevance
“…In a two-stage approach (also known as the standard meta-analysis approach), the study-specific effect sizes and standard errors are obtained or estimated from the included studies at the first stage, and then they are synthesized at the second stage [13,14]. Under the two-stage approach, available methods for zero-events include the continuity/empirical correction [7], Peto's OR [15], MH [16], two-stage Bayesian methods [17,18], the exact p-function method [19], the arcsine-based transformation (e.g., arcsine difference [20]), etc. Among these methods, Peto's OR is not applicable for dealing with double-zero-events studies.…”
Section: Rationale For the Classificationmentioning
confidence: 99%
“…In a two-stage approach (also known as the standard meta-analysis approach), the study-specific effect sizes and standard errors are obtained or estimated from the included studies at the first stage, and then they are synthesized at the second stage [13,14]. Under the two-stage approach, available methods for zero-events include the continuity/empirical correction [7], Peto's OR [15], MH [16], two-stage Bayesian methods [17,18], the exact p-function method [19], the arcsine-based transformation (e.g., arcsine difference [20]), etc. Among these methods, Peto's OR is not applicable for dealing with double-zero-events studies.…”
Section: Rationale For the Classificationmentioning
confidence: 99%
“…Finally, in this work, we accounted for but did not estimate between‐study variance. Due to the only two available studies, a proper estimation of the between‐study outcome variability is currently known to be almost nonfeasible 14‐17 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accounting for between-study variability may act as a less rough approach to minimize this decision-induced bias. A proper estimation of the between-trial early-phase outcome variance is not feasible with just two available studies, [14][15][16][17] therefore, in this article we choose not estimate but only account for this variance to aid towards the reduction of the bias.…”
Section: Bias Reduction By Accounting For Between-trial Early-phase Outcome Variabilitymentioning
confidence: 99%
“…On the other hand, Bayesian models are known for being sensitive to the choice of heterogeneity prior distributions in sparse settings, therefore, the need to identify priors with robust properties is crucial. Pateras et al [32] proposed a general way to set prior distributions. Via simulations, they showed that a uniform heterogeneity prior, bounded between -10 and 10, on the log heterogeneity parameter scale shows appropriate 95% coverage and induces relatively acceptable under/over estimation of both the overall treatment effect and heterogeneity, across a wide range of heterogeneity levels.…”
Section: Meta-analysismentioning
confidence: 99%